Dividing divided states - Treverton, Gregory F. (EBL-Schweitzer, 2014)
Dividing Divided States provides a detailed guide to recent secessions, from the partition of India to the secession of Eritrea from Ethiopia. This careful and straightforward study looks at the core issues likely to confront newly seceded states: people, natural resources, and state resources.